A preliminary study of fern diversity in UiTM Pahang forest reserve, Pahang - Musa, Nor Lailatul Wahidah; Zolkhoiry, Nurul Izzah; Shaikh Nasir, Nur Thabitah; Md Isa, Nurun Nadhirah; Nawi, Liliwirianis; Mohd Jan, Sarah Laila; Mohd Khazaai, Siti Nurhafiza (GADING Journal of Science and Technology, 2024)
The diversity of ferns (Pteridophyta) in UiTM Pahang Forest Reserve has not been widely reported, and thus the aim of this preliminary study is to assess the fern diversity and richness at UiTM Pahang Forest Reserve, Pahang. A total of 10 plots, sized of 10 × 10 m each, with a minimum distance of 20 m between each plot, were established at different locations using quadrat sampling method. A total of 330 individual ferns from 11 different species across 8 families were found in all sampled plots. Dicranopteris linearis, Nephrolepis biserrata and Thelypteris opulenta were observed to be the most abundant species, while Asplenium nidus were the least common species. The values of Shannon-Weiner biodiversity index (H’) and species richness index (IMargalef) in UiTM Pahang Forest Reserve were 2.22 and 1.73, respectively. The diversity index value indicated that the fern diversity in UiTM Pahang Forest Reserve is low, while the evenness index (E=0.84) also indicated that the number of individuals in each fern species is unevenly distributed. However, the low diversity of ferns in UiTM Pahang Forest Reserve could be regarded due to the small area being assessed in this study and therefore, an extensive survey should be employed to fully capture the diversity index value of this forest area.